Case Reports on the Differentiation of Malignant and Benign Intratracheal Lesions by 18F-FDG PET/CT. Issue 44 (November 2015) - Unknown
Abstract : Abstract: Malignant tracheal tumors (primary and secondary) are rare and benign tumors of the tracheobronchial tree are also rare. Few reports have been issued on the 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET) findings of tracheal tumors or benign nontumorous tracheal lesions, which have been mainly studied by computed tomography (CT). The author reports 2 cases of intratracheal lesions with quite different 18 F-FDG PET/CT findings. The first case was of a 73-year-old woman with colon cancer treated by hemicolectomy and subsequent adjuvant chemotherapy. Follow-up 18 F-FDG PET/CT after 6 years revealed a hypermetabolic fungating mass (SUVmax: 5.8) in the distal trachea and biopsy confirmed intratracheal metastasis. The second case involved a 61-year-old man with tongue cancer who underwent mouth floor mass excision and right supraomohyoid neck dissection with submental flap reconstruction. Tracheal lesion was incidentally found during a 18 F-FDG PET/CT follow-up study conducted 1 year later. A benign intratracheal condition with low FDG uptake (SUVmax: 1.2) and the lesion was not visualized by neck CT 4 months later. 18 F-FDG PET/CT uptake was helpful in differentiating benign and malignant intratracheal lesions.